Physical, morphological properties and raman spectroscopy of chestnut blight diseased castanea sativa mill. wood - Gündüz, Gökhan; Oral, Mehmet Ali; Akyüz, Mehmet; Aydemir, Deniz; Yaman, Barbaros; Aşık, Nejla; Bülbül, Ali Savaş; Allahverdi, Surhay; Aydemir, Deniz; Yaman, Barbaros (SCIELO, 2016)
In this study, some of the physical and anatomical properties of Chestnut Blight Diseased (CBD) wood were investigated, and the study also included observations using Raman spectroscopy. The objective of these investigations was to determine the extent of the damage that is done to the wood of the diseased chestnut trees, which must be removed from the forest and used in the manufacture of industrial products. It was indicated that most of the adverse effects of the disease were in the vascular cambium. There was a clear indication of deterioration of the wood in the last growth ring next to vascular cambium. In the diseased secondary xylem region next to vascular cambium; vessel diameter, vessel frequency and vessel element length had a decrease, and vessel and other cells were irregular compared to healthy wood. Spores were detected and identified as Cryphonectria parasitica (Murrill). Annual ring properties (annual growth ring width, latewood percentage, etc.) were similar in diseased wood compared to healthy wood. The Raman spectroscopy results showed no significant changes in the structure of the cell wall or its components. After removing the diseased parts, unlimited usage of formerly wood is possible. Heat treatment of the wood is suggested before use in the interest of sanitation and dimensional stability.
Keywords: Cambium; Chestnut Blight; SEM-EDX; Castanea sativa Mill; Raman spectroscopy